2019
DOI: 10.3233/prm-180581
|View full text |Cite
|
Sign up to set email alerts
|

The Eating and Drinking Ability Classification System for cerebral palsy: A study of reliability and stability over time

Abstract: This study evaluated the inter-observer reliability and stability over time of the Eating and Drinking Ability Classification System (EDACS) for children and young people with cerebral palsy (CP). Method: Case-records for 97 children with CP were examined to collect retrospective data about eating and drinking abilities, at four time-points, minimum 2 years between each time-point. Sex, Gross Motor Function Classification System (GMFCS) level, presence of feeding tube and orthopaedic issues were recorded from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 43 publications
(50 reference statements)
1
11
0
1
Order By: Relevance
“…The relationship between the EDACS levels for the children in the study, and the GMFCS and MACS was similar to that observed in other studies [9,16,24]. There was a moderate positive correlation; close examination of differences reveals that in 20% of cases, there was a difference of more than two levels in either direction.…”
Section: Relationships Between the Edacs And Other Functional Classification Systemssupporting
confidence: 87%
See 2 more Smart Citations
“…The relationship between the EDACS levels for the children in the study, and the GMFCS and MACS was similar to that observed in other studies [9,16,24]. There was a moderate positive correlation; close examination of differences reveals that in 20% of cases, there was a difference of more than two levels in either direction.…”
Section: Relationships Between the Edacs And Other Functional Classification Systemssupporting
confidence: 87%
“…Secondly, there were 38 participants (72%) under 6 years of age in our study. There is currently only limited evidence to support stability of EDACS levels for children with cerebral palsy over 3 years old [9]. It is possible that food and fluid textures suitable for much younger children continue to be given to older children with CP regardless of biting, chewing and swallowing abilities; routine assessment of eating, drinking and swallowing by registered health professionals such as speech and language therapists is not commonplace in the education institutions included in this study.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…EDACS se ha evaluado en estudios recientes en cuanto a su validez en distintas poblaciones pediátricas con PC demostrando muy buenos resultados de confiabilidad tanto entre profesionales como entre profesionales y familia [28][29][30] . Existe una alta asociación entre los niveles de EDACS con disfagia y dificultades al tragar, sin embargo la asociación entre el EDACS y el GMFCS es moderada [31][32][33] . Aún no son muchas las investigaciones que incorporan esta clasificación, pero se alienta su implementación para la valoración de la PC.…”
Section: Métodosunclassified
“…In addition, individuals with CP present motor disorders that can be accompanied by changes in sensation, cognition, communication, behavior, and perception [1,4]. These changes limit self-care functions, such as feeding and oral hygiene [4,5].…”
Section: Introductionmentioning
confidence: 99%